SCREENING ANTAGONISTIK ACTINOBACTERIA SEBAGAI AGEN BIOKONTROL TERHADAP Ganoderma boninense : Screening of antagonistic actinobacteria as biocontrol agent against Ganoderma boninense - Hasnaul Maritsa; Hesti Riany (Jurnal Silva Tropika, 2022)
ABSTRACT Actinobacteria (Actinomycetes) is a unique group among microbe and prokaryotes. They have both characteristics of fungi and bacteria. Actinobacteria could produce a wide range of secondary metabolites such as antibiotics, antifungal, antiprotozoal, antiviral, anticholesterol, antihelminth, anticancer, and immunosuppressant. It may cause a better combination as a biocontrol agent for plants. This research aimed to investigating potential actinomycetes as biocontrol agents of fungal plant pathogens, especially Ganoderma boninense. The method in this research consists of a few steps. Those are samples collection from soil and water in the primer forest and plantation soil (palm oil), samples isolation, actinobacteria characterization, and evaluation of the antifungal activity. The result has shown that 29 fungal isolates were found in this study. The percent growth inhibition (PGI) of actinobacteria isolates variated from 0-81,58%. And their inhibition mechanisms were antibiosis and competition. Keywords: actinomycetes, antimicrobial, fungal plant pathogen Â  ABSTRAK Actinobacteria (Actinomycetes) adalah kelompok unik dari kelompok mikroba dan prokariota. Actinobacteria memiliki karakteristik jamur dan bakteri dan dapat menghasilkan berbagai metabolit sekunder seperti antibiotik, antijamur, antiprotozoal, antivirus, antikolesterol, antihelminth, antikanker, serta imunosupresan. Kemampuanya ini dapat dimanfaatkan untuk campuran pada agen biokontrol tanaman. Penelitian ini bertujuan untuk mengetahui potensi aktinomisetes sebagai agen biokontrol jamur patogen tanaman, khususnya Ganoderma boninense. Metode dalam penelitian ini terdiri dari beberapa langkah, yaitu pengambilan sampel dari tanah dan air di hutan primer dan tanah perkebunan (kelapa sawit), isolasi sampel, karakterisasi aktinobakteri, dan evaluasi aktivitas antijamur. Hasil penelitian ini menunjukkan bahwa 29 isolat jamur yang ditemukan. Persentase hambatan pertumbuhan (PGI) isolat aktinobakteri bervariasi antara 0-81,58%. Dan mekanisme penghambatannya adalah antibiosis dan kompetisi. Â Kata kunci: actinomycetes, antimikroba, jamur patogen tanaman